Case Report: Burden of Illness in Narcolepsy Type 1: Hikikomori in a Teenage Girl - Filardi, Marco; Blunda, Vincenza; Vandi, Stefano; Musetti, Alessandro; Posar, Annio; Visconti, Paola; Pizza, Fabio; Plazzi, Giuseppe; Franceschini, Christian (Frontiers in Psychology, 2021)
Narcolepsy type 1 deeply impacts on quality of life, especially during adolescence, with NT1 children and adolescents that frequently report difficulties in integration with peers and decreased participation in after-school activities. Here we describe the case of an NT1 teenager girl presenting with severe physical and social withdrawal, fulfilling the proposed diagnostic criteria for hikikomori, together with the classic NT1 symptoms. Social withdrawal is an overlooked phenomenon among NT1 children and adolescents that, if present, require a multidisciplinary approach and personalized interventions, but patients can benefit from NT1 pharmacological treatment.